The Relationship Between Depressive/Anxiety Symptoms During Pregnancy/Postpartum and Sexual Life Decline after Delivery. (22nd February 2013) - Faisal‐Cury, Alexandre; Huang, Hsiang; Chan, Ya‐Fen; Menezes, Paulo Rossi
Abstract: Introduction: Several factors have been found to be independently associated with decline in sexual activity after delivery. However, the association between depression in pregnancy/postpartum and sexual problems is less clear. Aim: To prospectively evaluate the relationship between depressive/anxiety symptoms (DAS) during the perinatal period and sexual life in the postpartum period. Methods: A prospective cohort study conducted between May 2005 and March 2007 included 831 pregnant women recruited from primary care clinics of the public sector in São Paulo, Brazil. Four groups with DAS during antenatal and postpartum periods were identified using the Self Report Questionnaire (SRQ‐20): absence of both antenatal and postpartum DAS; presence of antenatal DAS only; presence of postpartum DAS only; and presence of both antenatal and postpartum DAS. The primary outcome was perception of sexual life decline (SLD) before and after pregnancy/delivery. Crude and adjusted risk ratios (RR), with 95% confidence intervals (95% CI), were calculated using Poisson regression to examine the associations between DAS and SLD. Main Outcome Measure: The main outcome measure of this study is the perception of SLD before and after pregnancy/delivery. Results: SLD occurred in 21.1% of the cohort. In the multivariable analysis, the following variables were independently associated with SLD: DAS during both pregnancy and postpartum (RR: 3.17 [95% CI: 2.18–4.59]); DAS during only the postpartum period (RR: 3.45 [95% CI: 2.39–4.98]); a previous miscarriage (RR: 1.54 [95% CI: 1.06–2.23]); and maternal age (RR: 2.11 [95% CI: 1.22–3.65]). Conclusions: Postpartum women with DAS have an increased likelihood for SLD up to 18 months after delivery. Efforts to improve the rates of recognition and treatment of perinatal depression/anxiety in primary care settings have the potential to preserve sexual functioning for low‐income mothers.